(untitled) (Forum Penelitian Agro Ekonomi, 2016)
The Arenga pinnata palm trees do not only produce sap but also multipurpose products, such as edible fruits, building materials, fibers, and wax. Palm sugar agribusiness development copes with both technical and non technical constraint, e.g. low-skilled farmers, low yield, and less value added. To improve farmer’s capacity there are some steps to take, namely: (a) technical and management training, (b) provision of improved seed and processing unit equipments, (c) institutional and marketing empowerment, and (d) implementing better aren farming system. Furthermore, to increase farmer’s bargaining position it is essential to strengthen farmers’ groups through collective marketing system with farmers’ groups association, as well as farmers’ skill enhancement.